Hepatitis B Reactivation in Immunosupressed Patients, Prophylaxis and Management - Ulfa Kholili; Tri Yanti (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Hepatitis B virus (HBV) reactivation is a clinical problem associated with high morbidity and mortality rates. Currently, this incidence seems to be increasing around the world. The reactivation commonly developes in immunosuppressed individuals, although it may also occur spontaneously. Individuals who develop malignancy with chronic hepatitis B virus infection are at high-risk for hepatitis B virus reactivation, since they are closely related to immunosuppression, especially when undergoing chemotherapy. The loss of immune control in these patients may results in the reactivation of HBV replication within hepatocytes. This review article will focus on HBV reactivation related to immunosuppressed patients, immunosuppressive drug classes and corresponding risk estimates of hepatitis B virus reactivation, screening test recommended before getting this drugs, choice of antiviral drugs for prophylaxis, and duration of prophylaxis treatment based on EASL, AASLD and APASL guidelines.